(untitled) (International Journal of Environmental Sciences, 2025)
Amitav Ghosh has emerged as one of the most compelling literary figures addressing the cultural and narrative challenges posed by climate change. His work occupies a vital space at the intersection of environmental literature, postcolonial critique, and climate fiction, offering readers a unique lens through which to engage with the Anthropocene. With a narrative style that blends history, myth, and global ecological consciousness, Ghosh’s fiction reveals the entanglement of environmental degradation with colonial legacies, global migration, and cultural memory. The article explores Ghosh’s contributions to environmental literature by examining both his fictional and nonfictional engagements with climate change, particularly focusing on key works such as The Hungry Tide, Gun Island, The Great Derangement, and The Nutmeg’s Curse. It outlines how Ghosh reimagines nature as a dynamic agent, integrates indigenous knowledge systems and folklore, and reflects on the ethical implications of human-animal relationships and ecological justice. The discussion further highlights central themes in current scholarly interpretations, including the effectiveness of fiction in catalyzing environmental awareness and the tensions between literary elitism and accessibility. Attention is also given to underexplored areas in Ghosh scholarship, such as gendered ecological suffering, water politics, and the potential for interdisciplinary collaborations that connect literature with climate science and anthropology. In assessing both the accomplishments and challenges of Ghosh’s environmental vision, the article affirms literature’s continued potential to reframe ecological consciousness in an era of planetary crisis.